2021
DOI: 10.1007/s00432-021-03758-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of nutritional and inflammation-based risk scores in follicular lymphoma in the era of anti-CD20 targeted treatment strategies

Abstract: Background The composition of the tumor microenvironment (TME) is conditioned by immunity and the inflammatory response. Nutritional and inflammation-based risk scores have emerged as relevant predictors of survival outcome across a variety of hematological malignancies. Methods In this retrospective multicenter trial, we ascertained the prognostic impact of established nutritional and inflammation-based risk scores [Glasgow Prognostic Score (GPS), C-react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 62 publications
(85 reference statements)
1
8
0
Order By: Relevance
“…Follow-up was conducted by consulting hospitalization records and telephone interviews until March 2022, from initial diagnosis to follow-up deadline or date of death. Overall survival (OS) was defined as the time from the date of diagnosis to death or last observation for any cause, Progression-free survival (PFS) was defined as that from the date of diagnosis to first relapse, progression or death and date of the last follow-up ( 18 , 19 ). Progression of disease within 24 months was defined as POD24 ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…Follow-up was conducted by consulting hospitalization records and telephone interviews until March 2022, from initial diagnosis to follow-up deadline or date of death. Overall survival (OS) was defined as the time from the date of diagnosis to death or last observation for any cause, Progression-free survival (PFS) was defined as that from the date of diagnosis to first relapse, progression or death and date of the last follow-up ( 18 , 19 ). Progression of disease within 24 months was defined as POD24 ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…[84][85][86] Finally, in 209 patients with FL, a retrospective multicenter study showed prognostic impact of GPS on OS and PFS. 87…”
Section: Glasgow Prognostic Scorementioning
confidence: 99%
“…Based on the concentration of C‐reactive protein and albumin, GPS has been derived from patients with various types of cancer and validated in multiple cohorts 84–86 . Finally, in 209 patients with FL, a retrospective multicenter study showed prognostic impact of GPS on OS and PFS 87 …”
Section: Reviewmentioning
confidence: 99%
“…The cut-off values of Ki-67 for optimal risk stratification are discussed conversely [ 29 , 30 , 31 ]. Among a large spectrum of solid tumors and hematological malignancies, it has been shown that the Glasgow Prognostic Score (GPS) reflects a representative and handy tool to identify cancer patients at risk for both early progression and all-cause mortality [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. GPS examines two essential mechanisms of tumor growth, progression and aggressiveness.…”
Section: Introductionmentioning
confidence: 99%
“…GPS examines two essential mechanisms of tumor growth, progression and aggressiveness. The first is systemic inflammation (via the C-reactive protein) and the second is the nutritional status of a cancer patient (via albumin) at the initial diagnosis [ 35 ]. In recent years, the impressive predictive capabilities of both factors have been demonstrated in cancer patients.…”
Section: Introductionmentioning
confidence: 99%